For the following function \( f \), find the antiderivative \( F \) that satisfies the given condition. \[ f(\mathrm{u})=6 e^{\mathrm{u}}+8 ; F(0)=-8 \]
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To find the antiderivative \( F \) of the function \( f(u) = 6 e^u + 8 \), we first integrate \( f(u) \): \[ F(u) = \int f(u) \, du = \int (6 e^u + 8) \, du \] We can split the integral: \[ F(u) = \int 6 e^u \, du + \int 8 \, du \] Calculating each part, we have: \[ \int 6 e^u \, du = 6 e^u + C_1, \quad \text{and} \quad \int 8 \, du = 8u + C_2 \] Combining these results gives us: \[ F(u) = 6 e^u + 8u + C \] Now, we need to find the constant \( C \) using the condition \( F(0) = -8 \): \[ F(0) = 6 e^0 + 8(0) + C = 6 + C \] Setting this equal to the given condition: \[ 6 + C = -8 \] Solving for \( C \): \[ C = -8 - 6 = -14 \] Thus, the antiderivative \( F \) is: \[ F(u) = 6 e^u + 8u - 14 \] This function satisfies both the antiderivative condition and the initial value \( F(0) = -8 \).